2009
DOI: 10.1371/journal.pone.0006641
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Healthy Oldest-Old

Abstract: Individuals who live to 85 and beyond without developing major age-related diseases may achieve this, in part, by lacking disease susceptibility factors, or by possessing resistance factors that enhance their ability to avoid disease and prolong lifespan. Healthy aging is a complex phenotype likely to be affected by both genetic and environmental factors. We sequenced 24 candidate healthy aging genes in DNA samples from 47 healthy individuals aged eighty-five years or older (the ‘oldest-old’), to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…processes are rational candidates to search for variability linked to increased survival at oldest ages (Tazearslan et al 2012). To this respect, SIRT3 deserves attention both for its role in mitochondrial homeostasis, a fundamental aspect of cell physiology, and for the available data associating SIRT3 to survival in animal models or in the elderly (Benigni et al 2009;Halaschek-Wiener et al 2009;Rose et al 2003;Bellizzi et al 2005). We have decided to analyze an informative set of SNPs of SIRT3 gene in a prospective study (TRELONG) allowing us to have access to survival data over a 7-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…processes are rational candidates to search for variability linked to increased survival at oldest ages (Tazearslan et al 2012). To this respect, SIRT3 deserves attention both for its role in mitochondrial homeostasis, a fundamental aspect of cell physiology, and for the available data associating SIRT3 to survival in animal models or in the elderly (Benigni et al 2009;Halaschek-Wiener et al 2009;Rose et al 2003;Bellizzi et al 2005). We have decided to analyze an informative set of SNPs of SIRT3 gene in a prospective study (TRELONG) allowing us to have access to survival data over a 7-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…To this respect, our analysis reflects closely the correlation between SIRT3 and longevity in the Italian population in the real world. As in a previous genetic study performed in our laboratory where we had already investigated a panel of SIRT3 SNPs (Polito et al 2013), we decided to select from this panel those matching or tagging a list of SIRT3 genetic variants whose presence was highlighted in a population of Caucasian elderly, suggesting their involvement in a prosurvival background (Halaschek-Wiener et al 2009). Thanks to the existence of linkage disequilibrium blocks within SIRT3, we were able to choose a couple of SNPs from Polito et al (2012) (rs3825075 and rs4980329) that were linked to the SNPs rs511744 and rs11246020 reported by Halaschek-Wiener et al (2009; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As was argued previously (Karasik et al 2005), the longevity phenotype has several limitations for a quantitative genetic study: (a) only a small subset of a general population may be assigned a phenotype (Halaschek-Wiener et al 2009); (b) it is difficult to obtain a sufficiently large sample of parents and offspring who both possess extreme longevity; (d) lack of a control sample (such as blood samples from the average-lifespan individuals, born at the same time as centenarians) poses a problem for casecontrol comparison of allelic frequencies; and (e) most importantly, ultimate longevity may not be the phenotype of clinical interest. Quality of life in older age and/or duration of disease-and disability-free aging would be preferable to be brought to the center of attention.…”
Section: Gwas Approach For Aging Genes Discoverymentioning
confidence: 99%
“…Recent studies found that the level of DNA methylation varys under environmental influences such as nutrition statues and aging (Maier and Olek, 2002;Halaschek-Wiener et al, 2009;Haggarty et al, 2009;Barres and Zierath, 2011). Twin studies depicted that DNA methylation profiles and the expression level of their related genes were more divergent in older twins than in infant twins, which proved the influences of environmental factors mediated by DNA methylation on the expression of related genes over time (Fraga et al, 2005).…”
Section: Introductionmentioning
confidence: 99%